Software process quality: management and control - Kenett, Ron S.; Baker, Emanuel R. (New York: Marcel Dekker, 1999)
Using actual examples of software process improvement from the private sector and government, this work demonstrates how quality systems, measurement techniques and performance evaluations work. It presents a methodology for analyzing an ongoing software development process and establishing a rational plan for process improvement.
A framework for software quality -- Basics of quality management and continuous process improvement -- ISO 9000, SEI Capability Maturity Model (CMM), and continuous software process improvement -- Software measurements programs: strategies and implementation issues -- Quality of software products and documents -- Software reliability control -- Software review and inspection processes -- Software development mangement dashboards
Includes bibliography and index
Keywords: Quality Control -- Software